2021
DOI: 10.1590/1519-6984.224913
|View full text |Cite
|
Sign up to set email alerts
|

Domestication strategies for the endangered catfish species Pseudopimelodus mangurus Valenciennes, 1835 (Siluriformes: Pseudopimelodidae)

Abstract: Wild fish domestication can be considered a strategic approach to endangered species conservation, supporting studies and reducing economic and environmental costs. Three of the most important strategies in the domestication processes of fish are the adaptation of wild fish to captivity, the reproduction of the adapted fish and the production and maintenance of the young individuals. That being said, the present study is divided in three experiments: the 1st aimed to adapt wild Pseudopimelodus mangurus to capt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 19 publications
(19 reference statements)
1
2
0
Order By: Relevance
“…Making Senggarat fish one of the aquaculture products with farming activities is a very important activity that needs to be done to maintain the sustainability and availability of Senggarat fish so that it is not endangered. Is this consistent with what was said in [17] that wild fish domestication could be a strategic approach to protect endangered species. The status of sengarat fish farming is that wild fish are still being caught in the country, and there is no technology or effort to cultivate them.…”
Section: Domestication and Status Sengarat Fish Ramingsupporting
confidence: 88%
“…Making Senggarat fish one of the aquaculture products with farming activities is a very important activity that needs to be done to maintain the sustainability and availability of Senggarat fish so that it is not endangered. Is this consistent with what was said in [17] that wild fish domestication could be a strategic approach to protect endangered species. The status of sengarat fish farming is that wild fish are still being caught in the country, and there is no technology or effort to cultivate them.…”
Section: Domestication and Status Sengarat Fish Ramingsupporting
confidence: 88%
“…The difference between the Characiformes and Siluriformes species was evidenced during the embryonic development and larval stage. P. mangurus being a carnivorous species with predatory and competitive behavior (Arashiro et al 2020;Shiguemoto et al 2021), demonstrated rapid development of all organic systems compared to the larvae of Characiformes species, such as the differentiation of the structures of the primitive digestive tract, increasing in length and space in the lumen of the intestine a few hours after hatching. These events during the morphological development of P. mangurus are characteristic of carnivorous species (O'connell 1981; Chakrabarti et al 1995).…”
Section: Discussionmentioning
confidence: 99%
“…Wild fish adapted to aquaculture environment tend to experience a reproductive system disturbance, especially for female fish (Zohar & Mylonas, 2001). It could be caused by different and limitation of the rearing environments (Fobert et al, 2019), nutrient availability (Shiguemoto et al, 2021), egg substrates (Fukuda & Sunobe, 2017), pheromones, and environmental signals (Sorensen & Stacey, 2004) compared to its natural habitat. Aside from environmental manipulation, hormonal induction is reported to be the most successful method to stimulate the fish gonadal development for the domesticated fish.…”
Section: Introductionmentioning
confidence: 99%